MENINGKATKAN PENGETAHUAN MITIGASI BENCANA KEBAKARAN DI PANTI ASUHAN TANJUNG BARAT - Anisa Afianti Nur; Raden Roro Kirani Annisa Anjani; Ahmad Mufazzal Marga; Dhanifa Aldeana Maheswari; Annisa Anindita Rahmania; Putri Regita Miolda; Syafira Ratu Fauzi; Alisya Isma Anindita; Khairunnisa Hasan; Celika Fahrudina; Adella Delisa Putri; Keren Stelin Maliangkay; Agnes Gonxa Mulia Hera; Resa Listiani; Hafidz Alfarisi; Syalisa Syabil; Endah Pravita Putri Aldia Pratama; Salwa Salsabil; Prasetio Hadi Pratama; Alya Diah Ullhaque; Afif Amir Amrullah (Universitas Pahlawan Tuanku Tambusai, 2022)
A disaster is an unexpected event for everyone, it is impossible to know when and where the disaster will come, disaster will always stalk us no matter adults, elderly, or children. Fire is a type of disaster that can have a major impact on all living things. Mitigation is an effort to prevent or minimize the potential impact of a disaster event. Disaster mitigation education, especially in fire disasters, needs to be instilled from an early age. In addition, childhood is a golden period, so the orphanage is the main target of fire prevention and control programs. This activity aims to provide disaster mitigation education to orphanage children because high-rise building fires in Indonesia are a fairly frequent problem and must be taken seriously. Community service activities are carried out in the form of counseling regarding fire disaster mitigation at the Tanjung Barat Orphanage. The community service method carried out was given a pretest to 14 children consisting of boys and girls to measure their knowledge of Fire Disaster Management, followed by the delivery of materials, and games, and after that a posttest to determine the understanding of the 14 children towards the material provided. The results of the pretest showed an average target knowledge of 73.6 and the post-test results increased by an average of 86.4. Thus, it was concluded that the knowledge of the children at the Tanjung Barat Orphanage increased after being given the material on Fire Disaster Management. With this increase in knowledge, it is hoped that the children at the Tanjung Barat Orphanage can carry out Fire Disaster Management according to the correct procedures without any sense of fear. Keywords: Children, Counseling, Disaster Mitigation, Fire, Orphanage